Methanation catalyst, preparation method and application thereof, and methanation method
By using a catalyst support with high specific surface area and pore volume, combined with the nickel active component, the problem of insufficient mechanical strength of the methanation catalyst support is solved, high catalytic activity and stability are achieved, and the efficiency of the methanation reaction is improved.
Patent Information
- Application Number
- CN202311437833.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-31
AI Technical Summary
The mechanical strength of the existing methanation catalysts is insufficient, resulting in the catalyst being easily broken and the thermal stability and resistance to carbon deposits are poor.
The catalyst support with a large specific surface area and pore volume is used, and combined with the supported nickel active components, the mechanical strength and catalytic activity of the catalyst are improved through specific molding and impregnation methods.
The high mechanical strength, catalytic activity and stability of the catalyst are achieved, and the CO conversion rate and methane selectivity of the methanation reaction are improved.
Smart Images

Figure CN119909692A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalyst preparation, and in particular to a methanation catalyst and a preparation method and application thereof, and a methanation method. Background Art
[0002] The methanation reaction can reduce carbon monoxide and carbon dioxide to methane and water with hydrogen. During the reaction, the activity of the catalyst has a crucial impact on the methanation reaction speed and production capacity. In the medium-temperature and high-temperature methanation reaction, there are problems such as high reaction temperature, large heat flux, easy carbon deposition on the catalyst, and harsh hydrothermal environment. The methanation catalyst used is not only required to have high catalytic performance, but also has high requirements for the thermal stability, hydrothermal stability, anti-carbon deposition performance and mechanical strength of the catalyst.
[0003] In order to better exert the performance of the catalyst, higher requirements are placed on the physical and chemical indicators of the catalyst carrier. The catalyst carrier needs to have a larger specific surface area, larger pore volume, more suitable pore size and surface properties, and higher strength. In addition, the shape of the catalyst also plays a very important role in engineering applications (heat transfer, mass transfer, pressure drop, etc.).
[0004] When using a fixed bed reactor for methanation reaction, in order to reduce pressure drop, the fixed bed has certain requirements on the catalyst particle size and particle shape, so that the catalyst bed has a high porosity after loading and reduces the pressure drop. Extrusion molding is a highly efficient and relatively low-cost molding method. It is easier to obtain a medium-strength carrier when extruding materials with smaller particle diameters, but it is difficult to obtain a high-strength carrier when extruding larger particle diameters.
[0005] Therefore, it is necessary to develop a methanation catalyst that has both high catalytic activity and high stability in the methanation reaction, and whose resistance to high temperature hydrothermal environment, specific surface area, stable pore structure and mechanical strength meet industrial needs. Summary of the invention
[0006] The purpose of the present invention is to overcome the problem that the mechanical strength of the carrier of the methanation catalyst in the prior art is insufficient, which makes the prepared catalyst easy to break and has poor thermal stability and anti-carbon deposition ability. A methanation catalyst and its preparation method and application, and a methanation method are provided. The carrier of the catalyst has a large specific surface area and pore volume, and the catalytic activity and selectivity of the catalyst can be improved in combination with the loaded nickel active component. At the same time, the catalyst has a high average mechanical strength and has a high CO conversion rate and methane selectivity when applied to the methanation reaction.
[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a methanation catalyst, wherein the methanation catalyst comprises a catalyst carrier and a nickel active component;
[0008] Based on the total mass of the methanation catalyst, the mass percentage of the catalyst carrier is 80-90wt%, and the mass percentage of the nickel active component in terms of oxide is 10-20wt%;
[0009] The average mechanical strength of the catalyst carrier is 35-80N / mm;
[0010] The particle mechanical strength dispersion coefficient of the catalyst carrier is in the range of 0-0.55.
[0011] A second aspect of the present invention provides a method for preparing a methanation catalyst, wherein the method comprises:
[0012] (1) mixing a carrier precursor with a peptizing agent, and then molding and calcining to obtain a catalyst carrier;
[0013] (2) impregnating the catalyst support in a solution containing a nickel compound and calcining the solution to obtain a methanation catalyst;
[0014] Wherein, the temperature change of the material before and after molding is less than 15°C.
[0015] The third aspect of the present invention provides a methanation catalyst prepared by the preparation method described in the second aspect.
[0016] A fourth aspect of the present invention provides a use of the methanation catalyst described in the first aspect or the third aspect in a methanation reaction.
[0017] A fifth aspect of the present invention provides a methanation method, wherein H2 / CO feed gas is contacted with the methanation catalyst described in the first aspect or the third aspect to carry out a methanation reaction.
[0018] Through the above technical solution, the beneficial effects obtained are as follows:
[0019] (1) The methanation catalyst provided by the present invention has high average mechanical strength and high catalytic activity and catalytic stability in the methanation reaction;
[0020] (2) In the present invention, the preparation method of the methanation catalyst is simple, which improves the mechanical strength of the catalyst carrier while ensuring that the catalyst carrier has a high specific surface area and pore volume, providing active sites for the loading and dispersion of the nickel active component, thereby improving the catalytic activity of the methanation catalyst; the methanation catalyst is used for the methanation reaction, which can ensure a high CO conversion rate and a high CH4 selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is an appearance diagram of the butterfly-shaped extruded strip obtained in Example 1;
[0022] Figure 2 It is a schematic diagram of the mechanical strength distribution of the carriers of Example 2, Example 6 and Comparative Example 3. DETAILED DESCRIPTION
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] A first aspect of the present invention provides a methanation catalyst, wherein the methanation catalyst comprises a catalyst carrier and a nickel active component;
[0025] Based on the total mass of the methanation catalyst, the mass percentage of the catalyst carrier is 80-90wt%, and the mass percentage of the nickel active component in terms of oxide is 10-20wt%;
[0026] The average mechanical strength of the catalyst carrier is 35-80N / mm;
[0027] The particle mechanical strength dispersion coefficient of the catalyst carrier is in the range of 0-0.55.
[0028] In the present invention, the catalyst carrier has high mechanical strength, small dispersion coefficient, and concentrated mechanical strength distribution. The methanation catalyst prepared by using the catalyst carrier has strong adaptability and has high CO conversion rate and methane selectivity for methanation reaction.
[0029] In the present invention, the dispersion coefficient refers to the dispersion of mechanical strength of catalyst carrier particles, which is the ratio of the standard deviation of the mechanical strength values of a group of catalyst carrier particles to their average value. The number of particles of the catalyst carrier is n, n is 15-30, and the dispersion coefficient of mechanical strength of the catalyst carrier particles is in the range of 0-0.55.
[0030] According to the present invention, preferably, the catalyst carrier particle mechanical strength dispersion coefficient is in the range of 0-0.55, for example, 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.52, 0.55, or any range between two thereof, preferably in the range of 0.15-0.52.
[0031] In the present invention, the average mechanical strength refers to the average value calculated from the compressive strength of 22 catalyst carrier particles tested. The compressive strength is measured by measuring the side crushing mechanical strength.
[0032] According to the present invention, preferably, based on the total mass of the methanation catalyst, the mass percentage of the catalyst carrier is 81-89 wt %, and the mass percentage of the nickel active component calculated as oxide is 11-19 wt %.
[0033] According to the present invention, the type of the catalyst carrier is not particularly limited, and the specific surface area, pore volume and average mechanical strength of the carrier can meet the limited range. Preferably, the catalyst carrier is selected from at least one of aluminum oxide, silicon dioxide, zirconium oxide, titanium dioxide, magnesium oxide, calcium oxide, silicon nitride, silicon carbide and carbon materials, preferably aluminum oxide.
[0034] According to the present invention, preferably, the average mechanical strength of the catalyst carrier is 38-75 N / mm.
[0035] According to the present invention, preferably, the specific surface area of the catalyst carrier is 60-130m 2 / g, for example 60m 2 / g, 70m 2 / g, 80m 2 / g, 90m 2 / g、100m 2 / g, 110m 2 / g, 120m 2 / g, 130m 2 / g, or any range between the two, preferably 70-120m 2 / g.
[0036] According to the present invention, preferably, the pore volume of the catalyst support is 0.3-0.6mL / g, such as 0.3mL / g, 0.35mL / g, 0.4mL / g, 0.45mL / g, 0.5mL / g, 0.55mL / g, 0.6mL / g, or any range therebetween, preferably 0.35-0.55mL / g. In the present invention, the specific surface area and pore volume of the catalyst support are measured by BET low temperature nitrogen adsorption method.
[0037] In the present invention, the catalyst carrier has a high specific surface area and a high pore volume, the nickel active component can be evenly dispersed in the carrier, and at the same time, the catalyst can be guaranteed to have a high average mechanical strength.
[0038] In the present invention, the particle diameter of the catalyst carrier is not particularly limited. Preferably, the particle diameter of the catalyst carrier is 3-20 mm, preferably 3.5-15 mm. It is easier to obtain high mechanical strength by molding a catalyst carrier with a smaller particle diameter. The larger the particle diameter of the catalyst carrier, the more difficult it is to improve the mechanical strength. In the present invention, the catalyst carrier has a large particle diameter while ensuring a high specific surface area, a high pore volume and a high mechanical strength.
[0039] In the present invention, the particle diameter of the catalyst carrier is measured by measuring the diameter of the circumscribed circle of the carrier cross section.
[0040] A second aspect of the present invention provides a method for preparing a methanation catalyst, wherein the method comprises:
[0041] (1) mixing a carrier precursor with a peptizing agent, and then molding and calcining to obtain a catalyst carrier;
[0042] (2) impregnating the catalyst support in a solution containing a nickel compound and calcining the solution to obtain a methanation catalyst;
[0043] Wherein, the temperature change of the material before and after molding is less than 15°C.
[0044] In the present invention, the preparation method of the methanation catalyst is simple, the raw material adaptability is strong, it is environmentally friendly, and it is easy to scale up industrially. The prepared methanation catalyst has high mechanical strength and has high CO conversion rate and high methane selectivity when used in methanation reaction.
[0045] In the present invention, the catalyst carrier has a large specific surface area and pore volume while ensuring that the carrier has high mechanical strength. The preparation method is simple and stable to operate, easy to industrially scale up, has strong raw material adaptability, and is environmentally friendly.
[0046] According to the present invention, preferably, the temperature change of the material before and after molding is less than 15° C., preferably less than 12° C. In the present invention, the temperature change of the material before and after molding is controlled to be small, and the deformation of the material caused by temperature change during the molding process is reduced, which helps to improve the average mechanical strength of the catalyst carrier.
[0047] According to the present invention, preferably, the molding temperature is 1-60°C, preferably 5-50°C; the molding pressure is 3-20MPa, preferably 4-15MPa. In the present invention, the molding temperature is controlled in a relatively low temperature range to avoid molding at a relatively high temperature, which will cause uneven heating of the outer surface and the inside of the particles of the molded product, excessively high outer surface temperature, and excessively low internal temperature, thereby reducing the mechanical strength of the obtained catalyst carrier.
[0048] According to the present invention, preferably, in step (1), the mixing further comprises adding water and a modification aid. The modification aid is an aid that can adjust the physical properties of the carrier and increase the alkalinity of the carrier. The modification aid can be directly added to the carrier precursor in the form of a metal oxide, or dissolved in water in the form of a metal compound and then added to the carrier precursor, or added to the catalyst carrier by impregnation.
[0049] According to the present invention, preferably, based on the weight of the carrier precursor being 1 g, the volume of water added is 0.6-1 mL, preferably 0.65-0.95 mL.
[0050] The inventors of the present invention have found that by adding a peptizing agent and a suitable modifying auxiliary agent during molding in combination with molding conditions, a high-strength carrier with a large specific surface area and pore volume can be obtained.
[0051] According to the present invention, preferably, the modification aid is selected from at least one of compounds containing alkali metal elements, alkaline earth metal elements and rare earth metal elements, preferably selected from at least one of oxides, carbonates, basic carbonates, organic salts, nitrates and hydroxides of alkali metal elements, alkaline earth metal elements and rare earth metal elements.
[0052] According to the present invention, preferably, the modification aid is selected from at least one of oxides and / or nitrates of alkaline earth metal elements and rare earth metal elements, and preferably selected from at least one of lanthanum nitrate, magnesium nitrate, zinc nitrate, potassium nitrate, magnesium oxide, calcium oxide, lanthanum acetate and magnesium acetate. In the present invention, the above-mentioned modification aid is used in combination with the carrier precursor and the peptizing agent to improve the stability of the carrier precursor, so that the carrier precursor is more moderate when dehydroxylation and / or phase transition occurs during calcination, which helps to maintain the specific surface area and pore volume of the catalyst carrier without affecting the mechanical strength.
[0053] In the present invention, preferably, the carrier and the modifying aid are of different material types.
[0054] According to the present invention, preferably, relative to 100 parts by weight of the carrier precursor, the amount of the modification aid added is 0.6-15 parts by weight, such as 0.6 parts by weight, 0.8 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 6 parts by weight, 8 parts by weight, 10 parts by weight, 12 parts by weight, 14 parts by weight, 15 parts by weight, or any range between the two, preferably 0.8-12 parts by weight. Too little modification aid added cannot achieve the effect of adjusting the physical properties of the carrier and increasing the alkalinity of the carrier; too much modification aid added affects the mechanical strength of the catalyst carrier and reduces the specific surface area of the carrier.
[0055] According to the present invention, preferably, the carrier precursor is a substance that is converted into a carrier by subsequent calcination. In the present invention, there is no particular limitation on the source of the carrier precursor, and those skilled in the art can select a conventional carrier precursor, which can be commercially available or prepared by an existing method, and can be converted into a carrier after calcination.
[0056] In the present invention, preferably, the carrier precursor is selected from at least one of alumina, metal aluminates, silicon dioxide, aluminosilicates, silicate minerals, titanium dioxide, zirconium oxide, magnesium oxide, zinc oxide, silicon nitride, silicon carbide and carbon materials. The alumina may be hydrated alumina and / or alumina colloid, and the aluminosilicate may be zeolite and / or kaolin.
[0057] According to the present invention, preferably, the carrier precursor is selected from at least one of pseudo-boehmite, calcium oxide and magnesium oxide.
[0058] According to the present invention, preferably, the carrier is selected from at least one of alumina, silica, zirconia, titania, magnesia, calcium oxide, silicon nitride, silicon carbide and carbon materials, preferably alumina.
[0059] In the present invention, preferably, alumina has the characteristics of large specific surface area, controllable pore structure, good thermal stability and strong adsorption capacity. Pseudo-boehmite is used as a carrier precursor to prepare the carrier. The prepared catalyst carrier has a higher specific surface area and pore volume, which is beneficial to the loading and dispersion of the active components, and the further prepared catalyst has a higher catalytic activity.
[0060] According to the present invention, the type of the peptizing agent is not particularly limited, and various peptizing agents conventionally used in the art can be used. Preferably, the peptizing agent is an organic acid and / or an inorganic acid, preferably selected from at least one of nitric acid, aluminum nitrate, acetic acid and citric acid, and more preferably a mixture of nitric acid and aluminum nitrate and / or citric acid. In the present invention, the addition of a peptizing agent can make the carrier precursor particles fully peptized, improve the mechanical strength of the formed catalyst carrier, and improve the pore structure.
[0061] According to the present invention, preferably, the amount of the peptizing agent added is 0.4-10 parts by weight, preferably 0.6-8 parts by weight, relative to 100 parts by weight of the carrier precursor. In the present invention, controlling the amount of the peptizing agent added within the above range can achieve the effect of both sufficient peptization and proper adjustment of physical properties, reducing waste and pollution.
[0062] According to the present invention, preferably, in step (1), the mixing further comprises adding an optional extrusion aid, an optional binder and an optional lubricant.
[0063] In the present invention, unless otherwise specified, the term "optional" means containing or not containing, adding or not adding, using or not using. Specifically, the present invention may add an extrusion aid or not add an extrusion aid. There is no particular limitation on the manner of adding each additive, and the additives may be added separately or together.
[0064] In the present invention, the type of the extrusion aid is not particularly limited, and can be a conventional extrusion aid in the art, preferably sesbania powder and / or cellulose. The amount of the extrusion aid is not particularly limited, and those skilled in the art can make adaptive adjustments as needed to ensure that subsequent molding is carried out smoothly. Preferably, relative to 100 parts by weight of the carrier precursor, the addition amount of the extrusion aid is 0-8 parts by weight, preferably 0-6 parts by weight.
[0065] In the present invention, preferably, the binder is an inorganic binder and / or an organic binder. The binder can play a role in binding the carrier precursor particles.
[0066] In the present invention, the type of the inorganic binder is not particularly limited, and can be any conventional inorganic binder in the art. Preferably, the inorganic binder is selected from at least one of cement, aluminum sol, silica sol, zirconium sol and titanium sol.
[0067] In the present invention, the type of the organic binder is not particularly limited, and can be any conventional organic binder in the art. Preferably, the organic binder is selected from at least one of methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose and microcrystalline cellulose.
[0068] In the present invention, the amount of the binder is not particularly limited, and those skilled in the art can adaptably choose whether to add the binder and the amount of the binder according to the mixing situation. Preferably, the amount of the binder added is 0-4 parts by weight, preferably 0.5-3 parts by weight, relative to 100 parts by weight of the carrier precursor.
[0069] According to the present invention, the type of the lubricant is not particularly limited, and can be a conventional lubricant in the art. Those skilled in the art can select the type and amount of the lubricant according to the adaptability of the molding effect. Preferably, the lubricant is selected from at least one of glycerol, polyol, polyester, magnesium stearate, stearic acid, talc and graphite.
[0070] In the present invention, preferably, the amount of the lubricant added is 0-10 parts by weight, preferably 0.1-5 parts by weight, relative to 100 parts by weight of the carrier precursor. In the present invention, the addition of the lubricant has a lubricating effect, which helps the smooth molding and can improve the average mechanical strength of the catalyst carrier in accordance with the molding conditions.
[0071] According to the present invention, preferably, the mixing includes dry mixing, kneading and / or mixing rolling. Preferably, the conditions of the kneading and / or mixing rolling include: the time of kneading and / or mixing rolling is 5-180 minutes, preferably 8-160 minutes.
[0072] According to a preferred embodiment of the present invention, the mixing process comprises: dry mixing the carrier precursor with the modification aid oxide, the optional extrusion aid, the optional binder and the optional lubricant for a certain period of time, and then adding an aqueous solution containing the modification aid and the peptizing agent, and mixing the above raw materials uniformly by kneading and / or mixing.
[0073] According to a preferred embodiment of the present invention, the molding method is selected from at least one of extrusion molding, compression molding and ball rolling molding. Those skilled in the art can select conventional molding equipment to perform the molding.
[0074] In the present invention, preferably, the extrusion molding method is adopted to produce a catalyst carrier having a higher specific surface area and pore volume and a higher mechanical strength, and has a higher preparation efficiency.
[0075] In the present invention, the shape of the product obtained by extrusion molding is not particularly limited. Preferably, it is selected from at least one of butterfly shape, cylindrical shape, clover shape, honeycomb shape, Raschig ring shape and porous special shape.
[0076] In the present invention, the material before molding also includes mixing the unqualified material that has been molded with water, mixing evenly by kneading and / or mixing and grinding, and then performing final molding. In the present invention, by mixing the molded product again, it is helpful to improve the product qualification rate. The unqualified material refers to the undried molded strips with rough surface, incomplete shape and average mechanical strength of less than 20N / mm after random inspection and roasting.
[0077] In the present invention, preferably, the weight ratio of the total mass of water added during the mixing process to the carrier precursor is 0.5-2.5:1, preferably 0.6-2:1, and more preferably 0.65-1.6:1.
[0078] In the present invention, preferably, the calcination further includes drying the formed product, and the drying conditions are not particularly limited, and those skilled in the art can select conventional drying methods and drying conditions. Preferably, the drying conditions include: a drying temperature of 30-180°C, preferably 45-160°C, more preferably 70-140°C; a drying time of 0.5-100 hours, preferably 1-80 hours, more preferably 2-70 hours. According to a preferred embodiment of the present invention, the drying process includes: drying at 30-70°C for 2-50 hours, and then drying at 100-150°C for 2-20 hours.
[0079] According to the present invention, preferably, the calcination conditions include: calcination temperature of 750-1150°C, preferably 850-1050°C; calcination time of 1-8 hours, preferably 2-6 hours; heating rate of 1-8°C / min, preferably 2-6°C / min. In the present invention, high temperature calcination is carried out under the above conditions, and the obtained catalyst carrier has a higher specific surface area.
[0080] In the present invention, the mass ratio of the catalyst carrier to the solution containing the nickel active component is not particularly limited, so that the mass percentage of the nickel active component calculated as oxide in the prepared methanation catalyst is 10-20wt%, and those skilled in the art can make adaptive adjustments according to the impregnation conditions.
[0081] According to the present invention, preferably, in the solution containing nickel compound, the mass concentration of nickel active component is 20-65wt%, preferably 25-60wt%. In the present invention, the above catalyst carrier is used in combination with the nickel active component, the nickel active component provides active sites, the mechanical strength of the catalyst carrier is high, and the prepared catalyst is used for methanation reaction, has high CO conversion rate and high methane selectivity, and can meet the requirements of long-term operation.
[0082] According to the present invention, the type of the nickel-containing compound is not particularly limited, and those skilled in the art can adaptably select a water-soluble nickel-containing compound. Preferably, the nickel-containing compound is selected from at least one of nickel nitrate, basic nickel carbonate, nickel formate and nickel acetate.
[0083] In the present invention, the average mechanical strength of the carrier and the definition of the dispersion coefficient of the mechanical strength of the particles are described in the above description and will not be repeated here.
[0084] According to the present invention, the impregnation conditions are not particularly limited, and those skilled in the art can select conventional impregnation conditions. Preferably, the impregnation conditions include: an impregnation temperature of 20-80°C, preferably 25-70°C; an impregnation time of 0.2-6 hours, preferably 0.5-4 hours.
[0085] In the present invention, preferably, the contact product is dried before calcination, and the drying conditions are not particularly limited. According to a preferred embodiment of the present invention, the drying comprises: vacuum drying the contact product for 0.5-4 hours, and then air drying at 80-150°C for 1-5 hours.
[0086] In the present invention, there is no particular limitation on the drying equipment, as long as it can achieve the drying effect. Preferably, the vacuum drying is performed in a rotary evaporator, and the air drying is performed in an oven.
[0087] According to the present invention, preferably, the calcination conditions include: a calcination temperature of 200-600° C., preferably 300-500° C.; and a calcination time of 1-8 hours, preferably 2-6 hours.
[0088] According to the present invention, preferably, based on the total mass of the methanation catalyst, the mass percentage of the catalyst carrier is 80-90wt%, preferably 81-89wt%, and the mass percentage of the nickel active component calculated as oxide is 10-20wt%, preferably 11-19wt%.
[0089] The third aspect of the present invention provides a methanation catalyst prepared by the preparation method described in the second aspect.
[0090] A fourth aspect of the present invention provides a use of the methanation catalyst described in the first aspect or the third aspect in a methanation reaction.
[0091] A fifth aspect of the present invention provides a methanation method, wherein H2 / CO feed gas is contacted with the methanation catalyst described in the first aspect or the third aspect to carry out a methanation reaction.
[0092] In the present invention, preferably, the methanation reaction conditions are: reaction pressure of 0.1-4 MPa, preferably 0.5-3 MPa; reaction temperature of 250-800°C, preferably 300-600°C; gas space velocity of 1000-150000 mL·g -1 ·h -1 , preferably 5000-100000mL·g -1 ·h -1 ; The volume ratio of H2 / CO is 1-4:1, preferably 2-3:1.
[0093] In the present invention, before the methanation catalyst is used, the methanation catalyst is also subjected to a reduction treatment, and the reduction treatment step comprises: placing the methanation catalyst in a reducing gas atmosphere at normal pressure for reduction, the reduction treatment temperature is 250-750°C, the reduction treatment time is 2-10 hours, and the reducing gas is H2 and / or an inert gas.
[0094] In the present invention, the methanation catalyst is subjected to a methanation reaction under the above conditions, and the catalyst has high catalytic activity and catalytic stability, as well as high CO conversion rate and high CH4 selectivity.
[0095] The present invention will be described in detail below through examples and comparative examples. In the following examples and comparative examples, unless otherwise specified, all reagents used are commercially available;
[0096] The screw extruder was purchased from the Science and Technology Industry General Factory of South China University of Technology, model F-26;
[0097] The test methods and test conditions for the specific surface area, pore volume, particle diameter and average mechanical strength of the catalyst carrier are described in the aforementioned specification and will not be repeated here.
[0098] Example 1
[0099] (1) Prepare a peptizing agent solution by weighing 2 g of citric acid and 6 g of lanthanum nitrate, adding 156 mL of water and 1.6 g of nitric acid with a mass concentration of 63%, and stirring to dissolve.
[0100] (2) 200 g of pseudo-boehmite powder (purchased from Sasol, dry basis 0.75) and 6 g of sesbania powder were dry mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder, and the mixture was kneaded for 10 min, mixed and rolled for 40 min to mix evenly, and then 4 mm butterfly strips were extruded on a screw extruder, and the molding temperature was controlled to be 45°C and the molding pressure was 6.5 MPa to obtain a molded product. The material temperature change before and after molding was 11°C. The molded product prepared above was dried at 120°C for 4 hours and calcined at 960°C for 4 hours, with a heating rate of 4°C / min, to obtain a catalyst carrier A1. Figure 1 This is an appearance diagram of an extruded strip of a catalyst carrier prepared in the example.
[0101] (3) Weigh 6.4 g of Ni(NO3)2·6H2O and 0.5 g of lanthanum nitrate and dissolve them in 12 g of deionized water, stir and dissolve to prepare an impregnation solution. Impregnate 10 g of the A1 carrier in the impregnation solution, let it stand for 1 hour, then place it on a rotary evaporator at 45°C for 1.5 hours, and then place it in an oven at 120°C for 2 hours. The dried sample is then placed in a muffle furnace and calcined at 400°C for 2 hours. The resulting catalyst is recorded as C1.
[0102] Comparative Example 1
[0103] The catalyst carrier was prepared according to the method of Example 1, except that the dry mixing time was 2 minutes and the mixing and grinding time was 10 minutes. The catalyst carrier was then molded according to the method of Example 1, the molding conditions were controlled to be consistent, and then dried and calcined to obtain the catalyst carrier D1.
[0104] The catalyst carrier has poor physical and chemical properties and is not selected for preparing catalysts.
[0105] Comparative Example 2
[0106] A catalyst carrier was prepared according to the method of Example 1, except that the extrusion temperature in step (2) was changed to 30° C., to obtain a catalyst carrier D2.
[0107] The catalyst carrier has poor physical and chemical properties and is not selected for preparing catalysts.
[0108] Example 2
[0109] (1) Prepare a peptizing agent solution by weighing 3 g of citric acid, 2 g of zinc nitrate, and 2 g of potassium nitrate, adding 166 mL of water and 1.6 g of nitric acid with a mass concentration of 63%, and stirring to dissolve.
[0110] (2) 200 g of pseudo-boehmite powder (purchased from Sasol, dry basis 0.75) and 6 g of sesbania powder were dry mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder, and the mixture was kneaded for 20 min, mixed and rolled for 40 min to mix evenly, and then 4 mm butterfly strips were extruded on a screw extruder, and the molding temperature was controlled to be 50°C and the molding pressure was 6 MPa to obtain a molded product. The material temperature change before and after molding was 11°C. The molded product prepared above was dried at 120°C for 4 hours and calcined at 960°C for 4 hours, with a heating rate of 4°C / min, to obtain a catalyst carrier A2.
[0111] (3) The catalyst carrier A2 was used to prepare a methanation catalyst according to the method of step (3) of Example 1. The obtained catalyst was recorded as C2.
[0112] Example 3
[0113] (1) Prepare a peptizing agent solution by weighing 11.12 g aluminum nitrate and 5 g magnesium nitrate, adding 165 mL water, and stirring to dissolve.
[0114] (2) 200 g of pseudo-boehmite powder (purchased from Sasol, dry basis 0.75) and 6 g of sesbania powder were dry mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder, and the mixture was kneaded for 20 min and mixed for 50 min; the obtained material was extruded into 4 mm butterfly strips on a screw extruder. The molding temperature was controlled to be 45°C and the molding pressure was 8 MPa to obtain a molded product. The temperature change of the material before and after molding was 7°C. The molded product prepared above was dried at 120°C for 4 hours and calcined at 1000°C for 4 hours with a heating rate of 4°C / min to obtain a catalyst carrier A3.
[0115] (3) The catalyst carrier A3 was used to prepare a methanation catalyst according to the method of step (3) of Example 1. The obtained catalyst was recorded as C3.
[0116] Example 4
[0117] (1) Prepare a peptizing agent solution by weighing 2.4 g of nitric acid with a mass concentration of 63%, adding 4 g of glycerol, 2 g of potassium nitrate and 6 g of lanthanum nitrate, adding 164 mL of water, and stirring to dissolve.
[0118] (2) 200 g of pseudo-boehmite powder (purchased from Sasol, dry basis 0.75) and 6 g of sesbania powder were uniformly mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder, the above mixture was kneaded for 20 min, mixed and rolled for 50 min, and 4 mm X-shaped strips were extruded on a screw extruder. The molding temperature was controlled to be 35° C. and the molding pressure was 8.5 MPa to obtain a molded product. The material temperature change before and after molding was 7° C. The molded product prepared above was dried at 100° C. for 4 hours and calcined at 960° C. for 4 hours at a heating rate of 4° C. / min to obtain a catalyst carrier A4.
[0119] (3) The catalyst carrier A4 was used to prepare a methanation catalyst according to the method of step (3) of Example 1. The obtained catalyst was denoted as C4.
[0120] Example 5
[0121] (1) Prepare a peptizing agent solution by weighing 2.4 g of nitric acid with a mass concentration of 63%, adding 6 g of a modification aid lanthanum nitrate, adding 162 mL of water, and stirring to dissolve.
[0122] (2) 200 g of pseudo-boehmite powder (purchased from Sasol, dry basis 0.75) and 10 g of sesbania powder, 5 g of modified auxiliary calcium oxide, and 2 g of methyl cellulose were uniformly mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder. The above mixture was kneaded for 80 min to mix evenly, and 4 mm butterfly strips were extruded on a plunger extruder. The molding temperature was controlled to be 45°C and the molding pressure was 9 MPa to obtain a molded product. The material temperature change before and after molding was 8°C. The above molded product was dried at 120°C for 4 hours and calcined at 1000°C for 4 hours at a heating rate of 3°C / min to obtain a catalyst carrier A5.
[0123] (3) The catalyst carrier A5 was used to prepare a methanation catalyst according to the method of step (3) of Example 1. The obtained catalyst was recorded as C5.
[0124] Example 6
[0125] (1) Prepare a peptizing agent solution by weighing 2.4 g of nitric acid with a mass concentration of 63%, adding 6 g of lanthanum nitrate, and adding 156 mL of water to stir and dissolve.
[0126] (2) 200 g of pseudo-boehmite powder (purchased from Sasol, dry basis 0.75) and 6 g of sesbania powder, 7 g of modified auxiliary magnesium oxide, and 4 g of methyl cellulose were uniformly mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder. The above mixture was kneaded for 5 min, and then the above mixture was mixed and rolled for 90 min to mix evenly, and 4 mm butterfly strips were extruded on a plunger extruder. The molding temperature was controlled to be 40°C and the molding pressure was 10 MPa to obtain a molded product. The material temperature change before and after molding was 9°C. The above molded product was dried at 120°C for 4 hours and calcined at 1000°C for 4 hours with a heating rate of 3°C / min to obtain a catalyst carrier A6.
[0127] (3) The catalyst carrier A6 was used to prepare a methanation catalyst according to the method of step (3) of Example 1. The obtained catalyst was denoted as C6.
[0128] Comparative Example 3
[0129] A catalyst carrier was prepared according to the method of Example 6, except that the mixing and grinding was performed for 20 minutes, the molding temperature was 35°C, the temperature change before and after molding was 6°C, and the molding pressure was 3.5 MPa, to obtain a catalyst carrier D3.
[0130] The catalyst carrier has poor physical and chemical properties and is not selected for preparing catalysts.
[0131] Comparative Example 4
[0132] The catalyst carrier was prepared according to the method of Example 6, except that the amount of nitric acid added was 4 g, the molding temperature was 55° C., the temperature change before and after molding was 16° C., and the molding pressure was 12.5 MPa. The catalyst carrier D4 was obtained. The orifice plate was damaged due to the high pressure, and the shape of some extruded strips changed. The catalyst carrier had poor physical and chemical properties and was not selected for preparing the catalyst.
[0133] Example 7
[0134] The unqualified extruded strips after molding in Comparative Example 1 were supplemented with 10 g of water and mixed and milled for 40 minutes. The obtained material was molded and dried and calcined according to the conditions of Example 1 to obtain catalyst carrier A7.
[0135] The catalyst carrier A7 was used to prepare a methanation catalyst according to the method of step (3) of Example 1. The obtained catalyst was recorded as C7.
[0136] Example 8
[0137] (1) Prepare a peptizing agent solution by adding 11.12 g of aluminum nitrate into 150 mL of water and dissolving the mixture.
[0138] (2) 200 g of pseudo-boehmite powder (purchased from Sasol) and 6 g of sesbania powder, 6 g of modified auxiliary magnesium oxide, and 2 g of calcium oxide were mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder, and then the above mixture was kneaded for 30 min, mixed and rolled for 70 min to mix evenly, and 6 mm butterfly strips were extruded on a plunger extruder. The molding temperature was controlled to be 35°C and the molding pressure was 5 MPa to obtain a molded product. The material temperature change before and after molding was 6°C. The above-prepared molded product was placed at room temperature for 24 h, dried at 90°C for 4 hours, and calcined at 1000°C for 4 hours. The heating rate was 2°C / min to obtain a catalyst carrier A8.
[0139] (3) The catalyst carrier A8 was used to prepare a methanation catalyst according to the method of step (3) of Example 1. The obtained catalyst was denoted as C8.
[0140] Example 9
[0141] (1) Prepare a peptizing agent solution by weighing 2.4 g of nitric acid with a mass concentration of 63%, 2 g of citric acid, adding 6 g of lanthanum nitrate, and adding 168 mL of water, stirring to dissolve.
[0142] (2) 200 g of pseudo-boehmite powder (purchased from Sasol) and 6 g of sesbania powder, 6 g of magnesium oxide, and 2 g of methyl cellulose were uniformly mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder, and the above mixture was kneaded for 30 min, mixed and rolled for 90 min to mix evenly, and 6 mm butterfly strips were extruded on a plunger extruder. The molding temperature was controlled to be 30°C and the molding pressure was 6.8 MPa to obtain a molded product. The material temperature change before and after molding was 6°C. The molded product was placed at room temperature for 48 hours, dried at 90°C for 4 hours, and calcined at 1000°C for 4 hours. The heating rate was 2°C / min to obtain a catalyst carrier A9.
[0143] (3) The catalyst carrier A9 was used to prepare a methanation catalyst according to the method of step (3) of Example 1. The obtained catalyst was denoted as C9.
[0144] Example 10
[0145] (1) Prepare a peptizing agent solution by weighing 6 g of nitric acid with a mass concentration of 63%, adding 6 g of lanthanum nitrate, adding 210 mL of water, and stirring to dissolve.
[0146] (2) Mix 200g of carbonized pseudo-boehmite powder (dry basis 0.7) and 6g of sesbania powder for 10 minutes, then add the prepared peptizing agent solution to the dry powder, knead the mixture for 30 minutes, and mix and grind for 80 minutes to mix evenly. The resulting material is extruded into 6 mm butterfly strips on a plunger extruder. The molding temperature is controlled to be 20°C and the molding pressure is 7MPa to obtain a molded product. The temperature change of the material before and after molding is 10°C. The above molded product is dried at 60°C for 24 hours, and the dried strip is calcined at 960°C for 4 hours at a heating rate of 2°C / min to obtain a catalyst carrier A10.
[0147] (3) The catalyst carrier A10 was used to prepare a methanation catalyst according to the method of step (3) of Example 1. The obtained catalyst was recorded as C10.
[0148] Embodiment 11
[0149] Prepare basic nickel carbonate impregnation solution and nickel salt solution: add 7.8 grams of ammonium carbonate to 11.7 grams of concentrated ammonia water, stir to dissolve, then add 3.25 grams of basic nickel carbonate, slowly heat to 45°C and stir until dissolved to obtain a nickel-containing impregnation solution. This impregnation solution is contacted with 10g of A6 carrier, and after standing for 1 hour, it is placed on a rotary evaporator and vacuum dried at 40°C for 1.5 hours, and then placed in an oven at 140°C for 2 hours. The dried sample is then placed in a muffle furnace and calcined at 450°C for 4 hours. The resulting catalyst is recorded as C11.
[0150] Test Example 1
[0151] The test results of the specific surface area, pore volume, average mechanical strength and dispersion coefficient of the prepared catalyst carrier are shown in Table 1. The dispersion coefficient is calculated by taking 22 particles of each group of catalyst carrier particles.
[0152] Table 1
[0153]
[0154]
[0155] It can be seen from Table 1 that the catalyst supports prepared in Examples 1-10 have significantly improved mechanical strength compared to Comparative Examples 1 and 2. It can be seen that the method for preparing a catalyst support provided by the present invention has a higher specific surface area and mechanical strength.
[0156] Figure 2 is a schematic diagram of the mechanical strength distribution of the carriers of Example 2, Example 6 and Comparative Example 3, from Figure 2 It can be seen that the method for preparing a catalyst carrier provided by the present invention not only has high mechanical strength, but also has low strength dispersion, which is beneficial for the catalyst to maintain stable mechanical strength during application and improve practicality.
[0157] Test Example 2
[0158] The C1-C11 catalysts were sieved to 10-20 mesh and 10 g of each was weighed and loaded into the reactor. They were reduced at 500 °C for 3 hours under normal pressure in a pure hydrogen atmosphere for activation. After the reduction, the temperature was lowered to 320 °C in a hydrogen atmosphere, and the raw gas (H2 / CO volume ratio of 3:1) was switched to react. The reaction space velocity was 10000 mL·g -1 ·h -1 , the reaction pressure is 2MPa. The tail gas composition was analyzed by gas chromatography online sampling, and the CO conversion rate and CH4 selectivity were calculated. The results are shown in Table 2.
[0159] Table 2
[0160]
[0161]
[0162] It can be seen from Table 2 that the catalyst prepared according to the high-strength carrier provided by the present invention has good catalytic performance and has a high CO conversion rate and CH4 selectivity.
[0163] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A methanation catalyst, characterized in that: The methanation catalyst contains a catalyst carrier and a nickel active component; Based on the total mass of the methanation catalyst, the mass percentage of the catalyst carrier is 80-90wt%, and the mass percentage of the nickel active component calculated as oxide is 10-20wt%; The average mechanical strength of the catalyst carrier is 35-80N / mm; The particle mechanical strength dispersion coefficient of the catalyst carrier is in the range of 0-0.
55.
2. The catalyst according to claim 1, wherein Based on the total mass of the methanation catalyst, the mass percentage of the catalyst carrier is 81-89wt%, and the mass percentage of the nickel active component calculated as oxide is 11-19wt%; Preferably, the catalyst carrier is selected from at least one of alumina, silica, zirconia, titania, magnesia, calcium oxide, silicon nitride, silicon carbide and carbon materials, more preferably alumina; Preferably, the average mechanical strength of the catalyst carrier is 38-75 N / mm; Preferably, the specific surface area of the catalyst carrier is 60-130m 2 / g, preferably 70-120m 2 / g; Preferably, the pore volume of the catalyst support is 0.3-0.6 mL / g, preferably 0.35-0.55 mL / g; Preferably, the particle mechanical strength dispersion coefficient of the catalyst carrier is in the range of 0.15-0.
52.
3. A method for preparing a methanation catalyst, characterized in that: The method comprises: (1) mixing a carrier precursor with a peptizing agent, and then molding and calcining to obtain a catalyst carrier; (2) impregnating the catalyst support in a solution containing a nickel compound and calcining the solution to obtain a methanation catalyst; Wherein, the temperature change of the material before and after molding is less than 15°C.
4. The preparation method according to claim 3, wherein The temperature change of the material before and after molding is less than 12°C; Preferably, in the solution containing nickel compound, the concentration of nickel active component is 20-65wt%, preferably 25-60wt%; Preferably, the nickel-containing compound is selected from at least one of nickel nitrate, basic nickel carbonate, nickel formate and nickel acetate; Preferably, the average mechanical strength of the catalyst carrier is 35-80 N / mm, preferably 38-75 N / mm; Preferably, the particle mechanical strength dispersion coefficient of the catalyst carrier is in the range of 0-0.55, preferably 0.15-0.
52.
5. The preparation method according to claim 3 or 4, wherein The impregnation conditions include: an impregnation temperature of 20-80°C, preferably 25-70°C; an impregnation time of 0.2-6 hours, preferably 0.5-4 hours; Preferably, the calcination conditions include: calcination temperature of 200-600°C, preferably 300-500°C; calcination time of 1-8 hours, preferably 2-6 hours; Based on the total mass of the methanation catalyst, the mass percentage of the catalyst carrier is 80-90wt%, preferably 81-89wt%, and the mass percentage of the nickel active component calculated as oxide is 10-20wt%, preferably 11-19wt%.
6. The preparation method according to any one of claims 3 to 5, wherein: In step (1), the mixing further comprises adding water and a modification aid; Preferably, based on the weight of the carrier precursor being 1 g, the volume of water added is 0.6-1 mL, preferably 0.65-0.95 mL; Preferably, the modification aid is selected from at least one of compounds containing alkali metal elements, alkaline earth metal elements and rare earth metal elements, preferably selected from at least one of oxides, carbonates, basic carbonates, organic salts, nitrates and hydroxides of alkali metal elements, alkaline earth metal elements and rare earth metal elements; Preferably, the modification aid is selected from at least one of lanthanum nitrate, magnesium nitrate, zinc nitrate, potassium nitrate, magnesium oxide, calcium oxide, lanthanum acetate and magnesium acetate; Preferably, relative to 100 parts by weight of the carrier precursor, the amount of the modification aid added is 0.6-15 parts by weight, preferably 0.8-12 parts by weight.
7. The preparation method according to any one of claims 3 to 6, wherein: The mixing includes dry blending, kneading and / or rolling; Preferably, the kneading and / or mixing conditions include: the kneading and / or mixing time is 5-180 min, preferably 8-160 min; Preferably, the molding conditions include: a molding temperature of 1-60° C., preferably 5-50° C.; and a molding pressure of 3-20 MPa, preferably 4-15 MPa.
8. The preparation method according to any one of claims 3 to 7, wherein: The carrier precursor is a substance that is converted into a carrier by subsequent calcination; Preferably, the carrier is selected from at least one of alumina, silica, zirconia, titania, magnesia, calcium oxide, silicon nitride, silicon carbide, and carbon materials; Preferably, the carrier precursor is selected from at least one of pseudo-boehmite, calcium oxide and magnesium oxide; Preferably, the peptizing agent is an organic acid and / or an inorganic acid, preferably at least one selected from nitric acid, aluminum nitrate, acetic acid and citric acid; Preferably, relative to 100 parts by weight of the carrier precursor, the added amount of the peptizing agent is 0.4-10 parts by weight, preferably 0.6-8 parts by weight.
9. The preparation method according to any one of claims 3 to 8, wherein: In step (1), the mixing further includes adding an optional extrusion aid, an optional binder and an optional lubricant; Preferably, the molding method is selected from at least one of extrusion molding, compression molding and ball rolling molding; Preferably, the calcination conditions include: a calcination temperature of 750-1150°C, preferably 850-1050°C; a calcination time of 1-8 hours, preferably 2-6 hours; a heating rate of 1-8°C / min, preferably 2-6°C / min.
10. The methanation catalyst obtained by the preparation method according to any one of claims 3 to 9.
11. Use of the methanation catalyst according to any one of claims 1 to 2 and 10 in a methanation reaction.
12. A methanation method, characterized in that: The H2 / CO raw gas is contacted with the methanation catalyst described in any one of claims 1-2 and 10 to carry out a methanation reaction.
Citation Information
Patent Citations
High-temperature methanation catalyst for producing natural gas through coal and preparation method of catalyst
CN103706370A
Methanation catalyst with magnesium-aluminium composite oxide as carrier and preparation method therefor
CN105013495A
Sulfur-tolerant methanation catalyst and preparation method thereof as well as magnesium aluminate spinel composite carrier and preparation method thereof
CN107398262A
Modification and preparation method for CO2 methanation novel nickel-based catalyst
CN108311154A
Carrier, supported catalyst, preparation methods and applications of carrier and supported catalyst, and method for preparing synthetic gas by dry reforming of methane
CN109718763A
Cited By
High-strength micro-particle-size methanation catalyst and preparation method thereof
CN120961182A